Understanding rapid implementation from discovery to scale: Rwanda's implementation of rotavirus vaccines and PMTCT in the quest to reduce under-5 mortality - Felix Sayinzoga; Lisa R. Hirschhorn; Jovial Thomas Ntawukuriryayo; Caroline Beyer; Kateri B. Donahoe; Agnes Binagwaho (BMC, 2024)
Abstract Background Over the last eight decades, many evidence-based interventions (EBIs) have been developed to reduce amenable under-5 mortality (U5M). Implementation research can help reduce the lag between discovery and delivery, including as new EBIs emerge, or as existing ones are adapted based on new research. Rwanda was the first low-income African country to implement the rotavirus vaccine (RTV) and also adopted Option B+ for effective prevention of mother-to-child transmission (PMTCT) before the World Health Organization's (WHO) recommendation. We use implementation research to identify contextual factors and strategies associated with Rwanda's rapid uptake of these two EBIs developed or adapted during the study period. Methods We conducted a mixed methods case study informed by a hybrid implementation research framework to understand how Rwanda outperformed regional and economic peers in reducing U5M, focusing on the implementation of health system-delivered EBIs. The research included review of existing literature and data, and key informant interviews to identify implementation strategies and contextual factors that influenced implementation outcomes. We extracted relevant results from the broader case study and used convergent methods to understand successes and challenges of implementation of RTV, a newly introduced EBI, and PMTCT, an adapted EBI reflecting new research. Results We found several cross-cutting strategies that supported the rapid uptake and implementation of PMTCT, RTV, and leveraging facilitating contextual factors and identifying and addressing challenging ones. Key implementation strategies included community and stakeholder involvement and education, leveraging of in-country research capacity to drive adoption and adaptation, coordination of donors and implementing partners, data audit and feedback of coverage, a focus on equity, and integration into pre-existing systems, including community health workers and primary care. The availability of donor funding, culture of evidence-based decision-making, preexisting accountability systems, and rapid adoption of innovation were facilitating contextual factors. Conclusion Implementation strategies which are generalizable to other settings were key to success in rapidly achieving high acceptability and coverage of both a new and an evolving EBI. Choosing strategies which leverage their facilitating factors and address barriers are important for other countries working to accelerate uptake of new EBIs and implement needed adaptations based on emerging evidence.